A comparison of depressive symptom profiles between current major depressive disorder and schizophrenia spectrum disorder. (March 2021) - Lange, Sjors M.M.; Schirmbeck, Frederike; Stek, Max L.; Murk Jansen, Yentl R.; van Rooijen, Geeske; de Haan, Lieuwe; Penninx, Brenda W.J.H.; Rhebergen, Didi; ,; Amelsvoort, Therese van; Bartels-Velthuis, Agna A.; Bruggeman, Richard; et al.
Abstract: Introduction: Depressive symptoms are highly prevalent and clinically relevant in schizophrenia spectrum disorder (SSD) patients. So far, little is known about to what extent the depressive symptom profile in SSD is comparable to that seen in major depressive disorder (MDD). Methods: Data were derived from the Genetic Risk and Outcome of Psychosis study (GROUP) and the Netherlands Study of Depression and Anxiety (NESDA). We examined differences in severity of depressive symptom profiles and distribution of mood/cognition and somatic/vegetative depressive symptoms using the Quick Inventory of Depressive Symptomatology - Self Report (QIDS-SR) within SSD patients (n = 449), MDD patients (n = 816) and healthy controls (n = 417), aged 18 to 50. Within SSD, associations between depression severity and clinical and demographic data were examined. Results: 60.4% of SSD patients showed substantial depressive symptomatology (QIDS-SR≥6). The difference in mood/cognition symptoms between SSD and MDD was larger (higher symptoms in MDD, effect size = 1.13), than the differences in somatic/vegetative symptoms (effect size 0.74). In patients with SSD, multivariable regression analyses showed that lower social functioning, male gender, use of benzodiazepine and more severe positive symptoms were associated with higher overall depressive symptomatology. The use of antipsychotics or antidepressants was associated with more somatic/vegetative symptoms. Conclusion: More than half of SSD patients have considerable depressive symptomatology, with a relative preponderance of somatic/vegetative symptoms compared to the profile seen in MDD. Future research could explore whether depressive symptom profile in SSD may also be associated with biological dysregulations like in MDD.